Invisible ink : a novel - Modiano, Patrick, 1945- (Margellos world republic of letters book., 2020)
The latest work from Nobel laureate Patrick Modiano, Invisible Ink is a spellbinding tale of memory and its illusions. Private detective Jean Eyben receives an assignment to locate a missing woman, the mysterious Noëlle Lefebvre. While the case proves fruitless, the clues Jean discovers along the way continue to haunt him. Three decades later, he resumes the investigation for himself, revisiting old sites and tracking down witnesses, compelled by reasons he can't explain to follow the cold trail and discover the shocking truth once and for all. -Amazon.